Controlling surface plasmon optical transmission with an electrochemical switch using conducting polymer thin films - Akira Baba (2018)
Surface plasmon resonance (SPR)-enhanced optical transmission is actively controlled by an electrochromism of conducting polymer thin films. Polyaniline and poly(3,4-ethylenedioxythiophene) thin films are deposited on a thin gold grating surface. SPR-enhanced optical transmission is demonstrated by irradiating white light on the conducting polymer thin film-gold grating surface and detecting the transmitted light from the back side. The transmission SPR system is combined with an electrochemical setup to manipulate the resonance. The wavelength of the sharp peak in the transmission light spectra is tuned by electrochemical doping/dedoping of the conducting polymer thin films. The present study of controllable SPR-enhanced optical transmission should provide novel active plasmonic devices such as active bandpass filters or biosensors. Surface plasmon resonance (SPR)-enhanced optical transmission is actively controlled by an electrochromism of conducting polymer thin films. The transmission SPR system is combined with an electrochemical setup to manipulate the resonance. The study of controllable SPR-enhanced optical transmission provides a pathway toward novel active plasmonic devices such as active band pass filters or biosensors. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.